Private and public in mass media communication: from letters to the editor to online commentaries - Landert, Daniela; Jucker, Andreas H. (Journal of pragmatics, 2011)
In recent years, the public and the private spheres have been blended in interesting ways. The mass media make the most private aspects of the lives of celebrities public and also the lives of ordinary people regularly feature in their publications. Letters to the editor (and more recently online commentaries) have always been a format for ordinary people to make their private voices heard in public. However, on the basis of data from The Times published in 1985 and from the Times Online published in 2008, we argue that in the development from the letters to the editor to the online discussion forums new configurations of public and private are discernible. This development affects the communicative situation, the content and the linguistic realization of the texts in different, albeit not independent ways. For the purpose of this argument it is necessary to develop a new communicative model that clearly distinguishes between the relevant dimensions of public and private. Koch and Oesterreicher (e.g. in Koch and Oesterreicher, 1985) developed a model of communication that relates the communicative situation to strategies of linguistic realization and distinguishes consistently between the phonic and graphic realization of language on the one hand, and between the language of immediacy and the language of distance on the other. This model will serve as the backdrop for our own model. We propose that their dimension of immediacy versus distance needs to be separated into three different dimensions. We, therefore, distinguish systematically between the communicative situation (the scale of public accessibility), the content (the scale of privacy) and the linguistic realization (the scale of linguistic immediacy). On the basis of this model it is possible to describe the traditional letters to the editor as being characterized by non-private contents and the language of distance while the discussion sections of recent online newspapers are characterized by private contents and the language of immediacy.